Toolkit for assessing and addressing cognitive health in early psychosis: Evaluation of feasibility and utility in a coordinated specialty care setting. Issue 5 (12th November 2020) - Saperstein, Alice M.; Medalia, Alice; Malinovsky, Igor; Bello, Iruma; Dixon, Lisa B.
Abstract: Aim: Methods to identify and harness individual cognitive strengths while addressing relative weaknesses have the potential to complement recovery services for first‐episode psychosis but systematic implementation is needed. We developed a cognitive health toolkit, trained teams from OnTrackNY, a network of coordinated specialty care (CSC) programs and examined toolkit feasibility and clinical utility during the first year of roll‐out. Methods: The toolkit includes a clinician manual, assessment and decision‐making tools, and a menu of cognitive health service options. Assessment uses the WRAT5‐Reading subtest and a new Self‐Assessment of Cognitive Functioning which, together, determine participant‐ and clinician‐perceived cognitive health need. Program‐level data were analysed for rates of assessment, identification of cognitive health needs and cognitive health service provision. Results: Data from 18 OnTrackNY teams included 933 participants, including 310 new admissions. Across teams, 43.9% of newly admitted participants received a WRAT5‐Reading and 41.3% received a self‐assessment. Of all assessments completed in the study period, 50.7% were at or within 3‐months of admission and 69.1% were within the first year of program participation. Cognitive health need was identified by self‐report (57.6%) and clinician‐report (69.9%) and led to provision of specific services, including psychoeducation, compensatory skills training and in some cases restorative cognitive training. Conclusions: Preliminary feasibility data are encouraging but barriers to assessment need to be identified and addressed. Rates of identified cognitive health need warrant further study of the implementation process and outcomes so that cognitive health assessment and treatment practices may ultimately be disseminated to CSC programs more broadly.